2021
DOI: 10.1080/13510002.2021.1901028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the protective effect of cytosolic and mitochondrial Peroxiredoxin 5 against glutamate-induced neuronal cell death

Abstract: Objectives: Although glutamate is an essential factor in the neuronal system, excess glutamate can produce excitotoxicity. We previously reported that Peroxiredoxin 5 (Prx5) protects neuronal cells from glutamate toxicity via its antioxidant effects. However, it is unclear whether cytosolic or mitochondrial Prx5 provides greater neuroprotection. Here, we investigated differences in the neuroprotective effects of cytosolic and mitochondrial Prx5. Methods: We analyzed patterns of cytosolic and mitochondrial H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It was found that Glu-induced cytotoxicity was associated with oxidative stress, mitochondrial imbalances, and autophagy imbalances 132 . Additionally, the apoptotic cell death caused by Glu toxicity was accelerated by mitochondrial dysfunction and ROS overproduction 133 . Therefore, Glu were selected as a damaging agent in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Glu-induced cytotoxicity was associated with oxidative stress, mitochondrial imbalances, and autophagy imbalances 132 . Additionally, the apoptotic cell death caused by Glu toxicity was accelerated by mitochondrial dysfunction and ROS overproduction 133 . Therefore, Glu were selected as a damaging agent in this study.…”
Section: Discussionmentioning
confidence: 99%